Native Valve Endocarditis due to Enterococcus hirae Presenting as a Neurological Deficit. (16th September 2013) - Anghinah, Renato; Watanabe, Rafael Gustavo Sato; Simabukuro, Mateus Mistieri; Guariglia, Carla; Pinto, Lécio Figueira; Gonçalves, Daniella Costa de Menezes e
Abstract : Enterococcus hirae is a rare isolate in clinical specimens. We describe a case of native aortic valve endocarditis in a 56-year-old man. This is the third reported case of endocarditis due to this organism, the first without recurrence of endocarditis and the first presenting as a neurological deficit.